Housing students with care and/or discipline : a study of a Swedish female-only student housing complex - Torisson, Fredrik (Critiques, 2026)
The actors providing housing to students have historically balanced precariously between the desire to care for students and the desire for disciplining them. These conflicting desires produce a tension between care and discipline that permeate institutions of student housing and their buildings. The following chapter traces how this tension played out in the formation and the first years of Sweden’s first purpose-built female-only student accommodation, Lunds studentskegård or the Lund Female Student Housing Estate (the LSG), inaugurated in 1937. The LSG is notable not only for its use, but even more so for the processes, negotiations and controversies through which it came to be and function. The building was the result of a tug-of-war between progressive student demands by individuals and feminist groups, and the more conservative dictates from actors within the university itself. The outcome was – and remains – an uneasy compromise that performs a unique balance between care and discipline that is shifted through subversive acts and tactics. The question addressed in this chapter is as follows: how was this balance between care and discipline negotiated between the actors, institutions and architecture involved? To date, this student housing complex has received very little attention in architectural historiography.
Keywords: Student housing; Care; Discipline